2019
DOI: 10.1111/jgh.14870
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic features of submucosal invasive non‐ampullary duodenal carcinomas

Abstract: Background and Aim: It is imperative to distinguish superficial non-ampullary duodenal carcinomas (NADCs) between intramucosal and submucosal invasive carcinoma for treatment selection. The aim of this study was to evaluate the clinicopathological differences of intramucosal and submucosal carcinoma. Methods: This was a retrospective, single-center study comprising 134 patients with 137 superficial NADCs during May 2005 and March 2018. Clinicopathological characteristics and treatment outcomes data were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
4
13
1
Order By: Relevance
“…These facts imply that gastric‐type duodenal neoplasms develop more frequently in the pre‐ampullary region and that GFM and HGM are precursors 16,19,23,24 . As to the biological features of gastric‐type and intestinal‐type malignant duodenal lesions, gastric‐type lesions have a higher frequency of HGN/SMC 24–26 and worse survival after resection than do intestinal‐type lesions 16 . In the current study, all gastric‐type lesions developed in the pre‐ampullary region, mostly adjacent to GFM and HGM, and 91% of them were HGN/SMC.…”
Section: Discussionsupporting
confidence: 45%
“…These facts imply that gastric‐type duodenal neoplasms develop more frequently in the pre‐ampullary region and that GFM and HGM are precursors 16,19,23,24 . As to the biological features of gastric‐type and intestinal‐type malignant duodenal lesions, gastric‐type lesions have a higher frequency of HGN/SMC 24–26 and worse survival after resection than do intestinal‐type lesions 16 . In the current study, all gastric‐type lesions developed in the pre‐ampullary region, mostly adjacent to GFM and HGM, and 91% of them were HGN/SMC.…”
Section: Discussionsupporting
confidence: 45%
“…We found that approximately half of SM-Ca lesions had a small diameter of �10 mm, which was higher compared to the 37% of M-Ca lesions measuring �10 mm; these findings are consistent with previous studies [5,19]. Furthermore, lesion diameter was similar between the SM-Ca and M-Ca groups (12 mm vs. 12 mm in diameter).…”
Section: Plos Onesupporting
confidence: 91%
“…We found that about one-half of SM-Ca had small diameter of ≤ 10 mm, which proportion was higher than that in M-Ca ≤ 10 mm (37%). A previous study also reported that 10-33% of SM-Ca were ≤ 10 mm in diameter [3,4]. These results indicate that there is the possibility of SM-Ca even in the small lesion ≤ 10 mm in diameter.…”
Section: Discussionsupporting
confidence: 63%
“…Takinami et al also reported that 58% were mixed macroscopic type among 12 lesions, but not signi cance between M-Ca and SM-Ca [4]. Regarding the macroscopic type for Ad-Ca, in our study, 5% were super cial, 8% were protruded, 79% were ulcerated, and 8% were sclerotic type among 84 lesions.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation